2021
DOI: 10.34119/bjhrv4n5-039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality of Root Canal Fillings Performed by Undergraduate Students of a Brazilian University / Avaliação da qualidade da obturação do canal radicular realizada por estudantes de graduação de uma Universidade brasileira

Abstract: The aim of this study was to evaluate the quality of root canal filling performed by undergraduate students at the Federal University of Espirito Santo (UFES). A total of 368 periapical radiographs of endodontic treatment performed by undergraduate students between 2012 and 2014 was assessment. The quality of root canal filling was based on two criteria: length of root canal filling and adequate density of the obturation. Root canal fillings were considered adequate if had no voids and were located at 0-2 mm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…A total of 114, 18, 8, and 53 published articles were excluded. Finally, 16 published papers were selected for full-text retrieval in the present systematic review study [9][10][11][12][13][22][23][24][25][26][27][28][29][30][31][32]. These studies measured the quality of RCFs and the overall quality treatments made by different treatment practicing settings (private, academic, and hospital) for different teeth types (anterior, premolar, and molar).…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 114, 18, 8, and 53 published articles were excluded. Finally, 16 published papers were selected for full-text retrieval in the present systematic review study [9][10][11][12][13][22][23][24][25][26][27][28][29][30][31][32]. These studies measured the quality of RCFs and the overall quality treatments made by different treatment practicing settings (private, academic, and hospital) for different teeth types (anterior, premolar, and molar).…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…Figure 2 and Table 1 present the characteristics of the 16 clinical studies included: 10 were conducted in 2023 [9][10][11]22,23] and 2021 [13,[26][27][28]30], 4 were published in 2022 [12,24,25,29], and a recent study was published in 2024 [32]. In relation to the study country, 8 studies were assessed in Saudi Arabia and Gulf countries [6,10,11,22,23,31], followed by 3, 2, 2, and 1 study documented in Brazil, Türkiye, Europe, and South Africa, respectively [9,12,13,22,[27][28][29]. Most of the studies [10] were performed in academic settings [9][10][11][12][22][23][24][25][26][27][28] followed by 3 hospital-based studies [13,30,31].…”
Section: Characteristics Of Included Clinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Endodontic treatment is necessary for a sizable part of dental emergencies treated globally, and there is a growing demand to train and educate dental students in this skill so they would be more ready to carry out such treatment with satisfactory outcomes [ 1 , 2 ]. However, numerous investigations have shown that general dentists do not deliver endodontic care of a high standard [ 3 – 4 ].…”
Section: Introductionmentioning
confidence: 99%